Presence of Group A streptococcus frequently assayed virulence genes in invasive disease: a systematic review and meta-analysis - Rampersadh, Kimona; Salie, M. Taariq; Engel, Kelin C.; Moodley, Clinton; Zühlke, Liesl J.; Engel, Mark E. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: It is currently unclear as to the role of Group A streptococcus (GAS) virulence factors (VFs) in contributing to the invasive potential of GAS. This work investigated the evidence for an association of GAS VFs with invasive disease.Methods: We employed a broad search strategy for studies reporting the presence of GAS VFs in invasive and non-invasive GAS disease. Data were independently extracted by two reviewers, quality assessed and meta-analysed using Stata®.Results: Thirty-two studies reported on 45 putative virulence factors (invasive (n=3236); noninvasive (n=5218), characterised by polymerase chain reaction (PCR), (n=30) and whole genome sequencing (WGS), (n=2). Risk of bias was rated as low, moderate, in twenty-three and nine studies, respectively. Meta-analyses of high-quality studies (n=23) revealed a significant association of speM [OR, 1.64 (95%CI, 1.06; 2.52)] with invasive infection. Metaanalysis of WGS studies demonstrated a significant association of hasA [OR, 1.91 (95%CI, 1.36; 2.67)] and speG [OR, 2.83 (95%CI, 1.63; 4.92)], with invasive GAS (iGAS). Metaanalysis of PCR studies indicated a significant association with speA [OR, 1.59 (95%CI, 1.10; 2.30)] and speK [OR, 2.95 (95%CI, 1.81; 4.80)] and invasive infection. A significant inverse association was observed in prtf1 [OR, 0.42 (95%CI, 0.20; 0.87)] and invasive infection.Conclusion: This systematic review and genomic meta-analysis provides evidence of a statistically significant association with invasive infection for the hasA gene, while smeZ, ssa, pnga3, sda1, sic, NaDase showed statistically significantly inverse associations with invasive infection. SpeA, speK and speG is associated with GAS virulence, however it is unclear if they are markers of invasive infection. This work could possibly aid in developing preventative strategies.